PENGEMBANGAN SELF HELP BOOK MINDFULNESS UNTUK MEREDUKSI STRES AKADEMIK PADA SISWA DI KELAS XI MAN 2 LEBAK - Maula Zulfiana Azhar; Evi Afiati; Rochani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop a self-help book media on how to reduce academic stress with mindfulness in class XI students of Man 2 Lebak. The research method used is Research & Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Based on the results of the academic stress questionnaire, it was found that most students were in the moderate academic stress category, but still needed services to help with these problems. The developed media was validated by three experts, namely material and media experts, language experts, and field practitioners. The results of the feasibility test showed that the media was declared very feasible, with an average feasibility score of 86%. A limited trial was conducted on 14 students with high levels of academic stress, students practiced mindfulness with 4 themes according to aspects of academic stress, namely biological, cognitive, emotional and social behavior and the results obtained that the media obtained a feasibility of 88%. The results of the pretest and posttest showed a decrease in the level of academic stress in all trial participants. Thus, the self-help book media is declared very suitable and effective for use as an innovative media in guidance and counseling services to help reduce academic stress in students.